Nome, immagine, gesto. Walter Benjamin tra linguaggio e tecnica - Rocca, Angelica (Mechane, 2024)
This paper aims to draw a path thorugh Benjamin’s philosophy of language in its relation with media and technics, finding a start point in “name” and an arrival in “gesture”. Reading the philosopher’s essay, On Language as such and on the Language of Man (1916), we can stretch one key subject of this philosophy: language as medium in which both men and nature communicate. Language is mostly community every being takes part to, against the “bourgeois” conception of language as simple means of signification. This idea bares theological and mystical references, but it can be also related to later developments of Benjamin’s work about technological reproducibility and its political uses. In the essay on language, the philosopher regards human “name” the translation for the mute language of things. Image and gesture, whose configurations are widely explored in Benjamin’s works about photography, cinema and radio, can be seen as translations too, exspecially for their political implications.